2017
DOI: 10.1155/2017/4832740
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Sequential Consensus in Networks: Analysis of Partially Connected Blockchains with Uncertainty

Abstract: This work presents a theoretical and numerical analysis of the conditions under which distributed sequential consensus is possible when the state of a portion of nodes in a network is perturbed. Specifically, it examines the consensus level of partially connected blockchains under failure/attack events. To this end, we developed stochastic models for both verification probability once an error is detected and network breakdown when consensus is not possible. Through a mean field approximation for network degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…It is computed using a random graph model where the connection probability between two randomly chosen nodes is "p" = Lmax/L, where Lmax=n(n-1)/2. Each curve ranges L from 1 to Lmax for each n. The dashed blue line represents the limit 0.7Lmax for n=10 (and Lmax=45) which is the minimum connectivity threshold found in [19]. Fig.…”
Section: Resultsmentioning
confidence: 96%
“…It is computed using a random graph model where the connection probability between two randomly chosen nodes is "p" = Lmax/L, where Lmax=n(n-1)/2. Each curve ranges L from 1 to Lmax for each n. The dashed blue line represents the limit 0.7Lmax for n=10 (and Lmax=45) which is the minimum connectivity threshold found in [19]. Fig.…”
Section: Resultsmentioning
confidence: 96%
“…A Trust-based routing algorithm was presented in Yang et al, 8 Christian et al, 9 Qiao et al, 10 Ren et al, 5 and Prieto-Castrillo et al, 11 which uses blockchain and reinforcement learning techniques toward data security in Wireless Sensor Network (WSN). A trusted model of the blockchain (BTM) was presented in She et al, 12 Shinde and Todkari, 13 and Iqbal et al, 14 to support data transmission and this method identifies the malicious node in three-dimensional space using the smart contract of blockchain in WSN.…”
Section: Related Workmentioning
confidence: 99%
“…However, given the limited resources, these nodes will store the "light" Blockchain-i.e., only block headers-and can connect to the full network as needed. In [15], the authors showed the possibility of creating a Blockchain for a partially connected network. This scheme can also be used in the work of mobile crews (patrols, checkpoints) of public services.…”
Section: Blockchain For a Databasementioning
confidence: 99%
“…Blockchain is a well-known technology used in Bitcoin [ 7 , 8 , 9 ] and other cryptocurrencies [ 10 , 11 ]. Successful attempts are also being made to introduce this technology in areas of bank transfers [ 12 ], logistics [ 13 ], energy [ 14 ], IoT [ 15 , 16 ], and healthcare [ 17 ]. We consider further the advantages and disadvantages Blockchain Technology.…”
Section: Introductionmentioning
confidence: 99%